Admission to child health surveillance lists: the views of FHSA general managers and general practitioners. Issue 6796 (27th July 1991) - Evans, A; Maskrey, N; Nolan, P
Abstract : OBJECTIVES–To find out the sources of advice that were helpful to managers of family health services authorities in drawing up the criteria for admission of general practitioners to the child health surveillance lists; to determine the criteria used for admission of general practitioners to the family health services authorities' child health surveillance lists; to find out the changes general practitioners have made in child health surveillance in their practices; to determine the experiences of general practitioners relating to admission to the child health surveillance lists and to training in child health surveillance. DESIGN–Survey by postal questionnaire. SUBJECTS–General managers of all family health services authorities in England and Wales; all general practitioners in Yorkshire and Humberside. RESULTS–Managers of 80 of 93 family health services authorities replied (86%). A total of 62 (78%) found local community paediatricians helpful in compiling criteria for admission to child health surveillance lists, and 46 (57%) found national guidelines helpful. Fifty seven (71%) accepted general practitioners who had completed an approved course, and 45 (56%) accepted those with three or more years' experience of child health surveillance. Of the 1966 questionnaires sent to general practitioners, 1233 were satisfactorily completed (63%). Of the 919 respondents who had applied to be put on child health surveillance lists, 673 (73%) had been permanently accepted; of these, 441 (65%) had done an approved course and 375 (56%) had had three or more years' experience of child health surveillance. Of the 145 (16%) not accepted, 57 (39%) had done an approved course and 71 (49%) had three or more years' experience. Respondents reported variable quality and availability of courses in child health. CONCLUSIONS–Acceptance of general practitioners on to child surveillance lists has not been carried out consistently despite national guidelines setting out criteria for acceptance.